Development of Digital-Based Learning Tools of Research Methodology Course in Early Childhood Teacher Education Department - Aman Simaremare; Roni Sinaga; Santa Murni A. Situmorang (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to develop digital-based learning tools in a research methodology course. The learning tools that were developed are modules. The development of this module is conducted through the Research and Development Method by Borg & Gall, the participant involved in the process of developing this learning module consists of material and media design experts, and students who have studied the research methodology course and students who are writing their undergraduate thesis. Data analysis using quantitative descriptive analysis.The final product is made after material and media design expert validation provides recommendations for testing in small groups and large groups. Testing results in the small group obtained an average value of 3.76 (good) and the large group with an average value of 3.70 (good). This indicates that digital-based learning tools in research methodology subject are already worth using. The learning module consists of module: 1. Research concept; 2. Types of research methods; 3. Research problems; 4. Theoretical foundation, thinking framework, and research hypothesis; 5. Research methodology, design, population, and sample; 6. Research data collection techniques and instruments; 7. Research data analysis techniques; 8. Writing research proposals according to the type of research method; 9. Compilation of research results, discussions, conclusions, and suggestions; and 10. Writing research reports according to the type of research method. The final product of the teaching material module is formatted in pdf. This research has limitations, where this research is preliminary so that further development is needed, besides that researchers also experience several obstacles to coordinating with the team directly due to the COVID 19 pandemic, but all are resolved by utilizing internet networks and technology to coordinate. The advantages of the products created make the products created have their own characteristics compared to other products, the modules developed from this research are very relevant to the needs of novice researchers such as students in writing a thesis, on the other side, the modules created are also support students to study online, during the COVID 19 pandemic.